Fast ignition relevant study of the flux of high intensity laser-generated electrons via a hollow cone into a laser-imploded plasma - Key, M; Adam, J; Akli, K; Borghesi, M; Chen, M; Evans, R; Freeman, R; Habara, H; Hatchett, S; Hill, J; Heron, A; King, J; et al. (2008)
An integrated experiment relevant to fast ignition. A Cu-doped deuterated polymer spherical shell target with an inserted hollow Au cone is imploded by a six-beam 900-J, 1-ns laser. A 10-ps, 70-J laser pulse is focused into the cone at the time of peak compression. The flux of high-energy electrons through the imploded material is determined from the yield of Cu Kα fluorescence by comparison with a Monte Carlo model. The electrons are estimated to carry about 15% of the laser energy. Collisional and Ohmic heating are modeled, and Ohmic effects are shown to be relatively unimportant. An electron spectrometer shows significantly greater reduction of the transmitted electron flux than is calculated in the model. Enhanced scattering by instability-induced magnetic fields is suggested. An extension of this fluor-based technique to measurement of coupling efficiency to the ignition hot spot in future larger-scale fast ignition experiments is outlined. © 2008 American Institute of Physics.